Prevalence and predictors of vitamin D deficiency in a nationally-representative sample of adults participating in the 2011-2013 Australian Health Survey - Malacova, Eva; Cheang, P.; Dunlop, E.; Sherriff, Jill; Lucas, R.; Daly, R.; Nowson, C.; Black, Lucinda (Cambridge University Press, 2019)
Vitamin D deficiency is recognised as a public health problem globally, and a high prevalence of deficiency has previously been reported in Australia. This study details the prevalence of vitamin D deficiency in a nationally representative sample of Australian adults aged ≥25 years, using an internationally standardised method to measure serum 25-hydroxyvitamin D (25(OH)D) concentrations and identifies demographic and lifestyle factors associated with vitamin D deficiency. We used data from the 2011–2013 Australian Health Survey (n 5034 with complete information on potential predictors and serum 25(OH)D concentrations). Serum 25(OH)D concentrations were measured by a liquid chromatography-tandem MS that is certified to the reference measurement procedures developed by the National Institute of Standards and Technology, Ghent University and the US Centers for Disease Control and Prevention. Vitamin D deficiency and insufficiency were defined as serum 25(OH)D concentrations <50 nmol/l and 50 to <75 nmol/l, respectively. Overall, 20 % of participants (19 % men; 21 % women) were classified as vitamin D deficient, with a further 43 % classified as insufficient (45 % men; 42 % women). Independent predictors of vitamin D deficiency included being born in a country other than Australia or the main English-speaking countries, residing in southern (higher latitude) states of Australia, being assessed during winter or spring, being obese, smoking (women only), having low physical activity levels and not taking vitamin D or Ca supplements. Given our increasingly indoor lifestyles, there is a need to develop and promote strategies to maintain adequate vitamin D status through safe sun exposure and dietary approaches.